(untitled) (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2018)
Fishermenâ€™s work is characterized by low and fluctuating income due to weather and season factors. Therefore, the wifeâ€™s productive work and income is important contribution to household income. The objectives of this study are to (1) Describe the fisherman wifeâ€™s characteristics, working roles, and income contribution ; (2) Analyze the relationship between characteristics and working roles of fishermanâ€™s wife; and (3) Analyze the relationship between characteristics and working role of fishermanâ€™s wife with their contribution to the household income. The research was conducted in Cidadap Village in Sukabumi using survey method and supported by qualitative data, and using a Chi-Square analysis test. Forty respondents were chosen purposively. The statistic test indicated that there is no relation between the characteristic of fishermanâ€™s wife with their working role, but both the type of wifeâ€™s work and the type of husbandâ€™s work were significantly related to the contribution of womenâ€™s income to the household. Key words: fisherman, fisherman wifeâ€™s working role ; wifeâ€™s contributionÂ to household income ABSTRAK Masyarakat nelayan sampai saat ini identik dengan kemiskinan dan pendapatan tidak menentu karena faktor cuaca dan musim, sehingga istri perlu bekerja produktif dan memberi kontribusi pendapatan untuk mencukupi kebutuhan rumah tangga. Tujuan penelitian ini adalah untuk (1) Mendeskripsikan karakteristik, peran kerja, dan kontribusi pendapatan istri nelayan; (2) Menganalisis hubungan antara karakteristik dengan peran kerja istri nelayan; serta (3) Menganalisis hubungan antara karakteristik dan peran kerja istri nelayan dengan kontribusi pendapatan rumah tangga. Penelitian ini dilaksanakan di Desa Cidadap dengan metode kuantitatif yaitu survei yang didukung data kualitatif, dan menggunakan uji analisis Chi Square. Responden sebanyak 40 orang dipilih secara purposive. Hasil penelitian ini menunjukkan bahwa karakteristik istri nelayan dengan peran kerja perempuan tidak memiliki hubungan, sedangkan karakteristik dan peran kerja istri nelayan yang berhubungan dengan kontribusi pendapatan perempuan adalah jenis pekerjaan perempuan dan pekerjaan suami. Kata kunci: Nelayan, Peran Kerja Istri Nelayan, Kontribusi Istri dalam Pendapatan Rumah Tangga